Quality of humus substances in sod-podzolic soil under different fertilization systems - Shovkun, O. O.; Popirny, M. A. (AgroChemistry and Soil Science, 2024)
The article presents the results of analytical studies of the quality of humus substances in sod-podzolic soil depending on the fertilization system. The relevance of the work is due to the need to develop effective approaches to increasing soil fertility by managing transformations of the quality of its organic matter (humus) components. Soil samples were taken in a field experiment established in 1990 on the territory of the Volyn State Agricultural Experiment Station in the Volyn region in the Polissya zone. The soil of the experimental site is sod-weakly podzolic clayey-sandy (Albic Arenosols). Experiment options selected for research: control (without fertilizers); manure 10 t/ha; manure in combination with mineral fertilizers or green manure; green manure. Methods for studying humic substances: (1) electron spectroscopy in the ultraviolet and visible ranges (200–600 nm) to assess the transformations of aromatic structures of humic acids; (2) gel permeation chromatography to study the molecular dispersion and structural organization of humic substances. The results of spectroscopic analysis showed that humic acids in soil from different fertilizer options are graphically characterized by the same type of inclined absorption line, which indicates the similarity of the structural organization of humic substances. The highest absorption intensity is observed in the UV range, which is associated with aromatic structures. Organic and organo-mineral fertilizer systems contributed to an increase in the concentration of stable aromatic compounds in humic acids. Chromatographic analysis revealed a bimodal distribution of molecular fractions of humic substances. The siderate and siderate+manure fertilization systems reduced the content of low-molecular aromatic structures in humic substances, which indicates their importance for increasing the stability of organic matter. It was established that fertilization systems significantly affect the quality of humic substances by changing the ratio of aromatic and hydrophilic structures. The features of the molecular heterogeneity of humic substances determine their stability in the soil. To improve the quality of organic matter (humus), it is necessary to take into account the transformations of low-molecular aromatic compounds and implement approaches that will contribute to the accumulation of organic carbon